Interrogating the Strategies of the Maccabees (2020)
The Maccabean revolt has elicited reactions in the arena of scholarly debates by experts in the various fields of Hellenistic civilization. Tcherikover, Hengel and Bicker have focused on the Seleucid-Jewish relations, the control of the Ptolemaic, Seleucid and Roman Empires over Judea, the probable causes of the Seleucid-Jewish wars and many other themes, with little attention paid to the strategies adopted by the Maccabees in their resistance against the Seleucid Empire, their victory over the Seleucid Empire and wresting her independence from the Empire. This paper, therefore, narrates the battle fought between the Seleucid Empire and the Jews, with a view to examining the strategies adopted by the Maccabees as she engaged the Seleucids for the control of their social, political and religious .£pace. The study employs the Foco Theory of Revolution as framework. The historical methodology is also adopted as it provides the trajectory of the battles, and the personalities of the chief instigators of the Seleucid and Maccabees' battles. Further studies that may examine the relationship between Antiochus IV Epiphanes and the Jewish High Priest, Jason are recommended.